A ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN SISTEM INFORMASI AKUNTANSI BERBASIS E-COMMERCE PADA APLIKASI PENJUALAN ONLINE DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Aulia, Dina (Universitas Prof.Hazairin,SH Bengkulu, 2023)
This study aims to determine and explain the influence of subjective norms, perceived convenience, perceived benefits and perceived complexity on the interest in using e-commerce-based accounting information systems in online sales applications among business people in the city of Sukabumi. The population of this study is the people of the city of Sukabumi with a sample of business actors in various fields that utilize e-commerce-based accounting information systems. The number of samples in this study were 50 respondents with data collection techniques, namely distributing questionnaires through the G-Form. The results of the questionnaire were processed using the SPSS 25 application. The results of this study indicate that subjective norms, perceived convenience, perceived usefulness and perceived complexity have no effect on interest in using e-commerce-based accounting information systems in online sales applications (a case study of business people in the city of Sukabumi).